Kemampuan Matematika Siswa Indonesia Berdasarkan TIMSS - Prastyo, Hendri (Jurnal Padegogik, 2020)
TIMSS stands for Trends in International Mathematics and Science Study. This activity aims to measure the mathematic and scient abilities of students in some countries. Indonesia is one of the TIMSS participating countries. This paper aims to determine the mathematic abilities of students in Indonesia as well as several factors that can improve students' mathematical abilities. The method used is a descriptive study of TIMSS results from 1999 to 2015. The results of this study indicate that the ability of Indonesian students is still at a low level (Indonesian students are only able to solve simple math problems) and there are several factors that need to be considered by the government, schools, and parents in order to improve the mathematical abilities of Indonesian students.